PENCEGAHAN KEKERASAN ANAK TERHADAP PRINSIP MANUSIA PANCASILA DEMI TERCIPTANYA KEADILAN - Subakdi, Subakdi (Inovasi Pembangunan : Jurnal Kelitbangan, 2023)
The future of a nation is determined by a child. Children who are part of the nation's successors should need protection to ensure harmonious physical, mental and social growth in order to avoid deviant behavior in accordance with Article 28B paragraph 2 of the 1945 Republic of Indonesia Law, every child has the right and obligation to build a nation and country. Therefore, the interests of children are highly prioritized to be protected from all forms of inhumane treatment, especially those that can result in violations of human rights. The fact is that the increase in violence against children in Indonesia is still a hotly discussed issue. The author uses a literature study method with a normative juridical approach with the aim of providing some insight into violence that occurs in children in relation to the human principles of Pancasila. The rise of violence against children is not only about human rights violations, but also violations of the values of the human principles of Pancasila, especially the second principle of just and civilized humanity and the fifth social justice for all Indonesian people.